The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1158/0008-5472.can-10-0296
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Expressing ErbB-2/neu Elicit Protective Antibreast Tumor Immunity In vivo, Which Is Paradoxically Suppressed by IFN-γ and Tumor Necrosis Factor-α Priming

Abstract: It is unknown whether mesenchymal stromal cells (MSC) can regulate immune responses targeting tumor autoantigens of low immunogenicity. We tested here whether immunization with MSC could break immune tolerance towards the ErbB-2/HER-2/neu tumor antigen and the effects of priming with IFN-γ and tumor necrosis factor-α (TNF-α) on this process. BALB/c-and C57BL/6-derived MSC were lentivirally transduced to express a kinase-inactive rat neu mutant (MSC/Neu). Immunization of BALB/c mice with nontreated or IFN-γ-pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…showed that MSCs expressing ErbB-2/neu elicited full protective antitumor immunity in vivo (43). In line with the above findings, we observed that MSC-L can prime antitumor immunity to control tumor.…”
Section: Discussionsupporting
confidence: 90%
“…showed that MSCs expressing ErbB-2/neu elicited full protective antitumor immunity in vivo (43). In line with the above findings, we observed that MSC-L can prime antitumor immunity to control tumor.…”
Section: Discussionsupporting
confidence: 90%
“…These cells function, in part, by providing a supportive stroma for the cancers and/or by participating in tumor vascularization (145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159). In contrast, MSCs and EPCs have been demonstrated to home to areas of tumor development, and engineered EPCs and MSCs, as well as Hematopoietic Stem Cells (HSCs), have been used to suppress tumor growth in mouse tumor models of primary lung cancers, metastatic lung cancers, and of other cancers metastatic to the lung (148,(160)(161)(162)(163)(164)(165)(166)(167)(168)(169)(170)(171)(172)(173)(174)(175)(176)(177)(178)(179). Cell based treatment may thus be useful in lung cancer therapeutics.…”
Section: Bronchioalveolar Stem Cellmentioning
confidence: 99%
“…Although the frequency of MSCs in the adult bone marrow is low (less than 0.1%), once isolated from bone marrow or from other tissues, MSCs can be expanded ex vivo, which makes it possible to manufacture these cells for potential therapeutic purposes. MSCs can also be relatively easily transduced or genetically manipulated to deliver or to secrete selected disease-modifying molecules (148,(161)(162)(163)(164)(165)(166)(167)(168)(169)(170)(171)(172)(173)(174)(175)(176)(177)(178)(179)(388)(389)(390). Overall, these properties of MSCs make them an attractive potential therapeutic tool as vectors for delivery of disease-specific treatment substances or as immunomodulatory agents.…”
Section: Structural Engraftment and Functional Effects Of Circulatingmentioning
confidence: 99%
“…In contrast to tumor-cytotoxic effects caused by acute local TNF-α administration, chronic and persistent presence of TNF-α in tumors has strong pro-tumoral effects in many cancers [19-21]. Accordingly, inhibition of TNF-α or its receptors has prominent anti-tumor effects in animal models of breast cancer [22-29]. In parallel, major causative pro-tumoral roles were attributed to IL-1β in breast cancer via angiogenesis and matrix-remodeling activities [30-37].…”
Section: Introductionmentioning
confidence: 99%